IGF1R signalling is a guardian of self-tolerance restricting autoantibody production - Erlandsson, Malin C.; Erdogan, Seval; Wasén, Caroline; Andersson, Karin M. E.; Silfverswärd, Sofia T.; Pullerits, Rille; Bemark, Mats; Bokarewa, Maria I. (Frontiers in Immunology, 2022)
Objective: Insulin-like growth factor 1 receptor (IGF1R) acts at the crossroad between immunity and cancer, being an attractive therapeutic target in these areas. IGF1R is broadly expressed by antigen-presenting cells (APC). Using mice immunized with the methylated albumin from bovine serum (BSA-immunized mice) and human CD14+ APCs, we investigated the role that IGF1R plays during adaptive immune responses. Methods: The mBSA-immunized mice were treated with synthetic inhibitor NT157 or short hairpin RNA to inhibit IGF1R signalling, and spleens were analysed by immunohistology and flow cytometry. The levels of autoantibody and cytokine production were measured by microarray or conventional ELISA. The transcriptional profile of CD14+ cells from blood of 55 patients with rheumatoid arthritis (RA) was analysed with RNA-sequencing. Results: Inhibition of IGF1R resulted in perifollicular infiltration of functionally compromised S256-phosphorylated FoxO1+ APCs, and an increased frequency of IgM+CD21+ B cells, which enlarged the marginal zone (MZ). Enlargement of MHCII+CD11b+ APCs ensured favourable conditions for their communication with IgM+ B cells in the MZ. The reduced expression of ICOSL and CXCR5 by APCs after IGF1R inhibition led to impaired T cell control, which resulted in autoreactivity of extra-follicular B cells and autoantibody production. In the clinical setting, the low expression of IGF1R on CD14+ APCs was associated with an involuted FOXO pathway, non-inflammatory cell metabolism and a high IL10 production characteristic for tolerogenic macrophages. Furthermore, autoantibody positivity was associated with low IGF1R signalling in CD14+ APCs. Conclusions: In experimental model and in patient material, this study demonstrates that IGF1R plays an important role in preventing autoimmunity. The study raises awareness of that immune tolerance may be broken during therapeutic IGF1R targeting.